Investigation of the free overfall for discharge measurement in stone bed triangular channels - Bahzad Mohammad Ali Noori; Chnen Jalal Mohammed (Ain Shams Engineering Journal, 2024)
This study utilizes the freefall as a simple and useful tool for measuring end depth discharge EDD in triangular channels having stone beds. For this task, forty-five triangular channel models are constructed and examined all having 360 cm length and end drop fall of 20 cm. In these channel models, three channel side slopes z = 0.7, 1.0 and 1.3, five bed slopes St = 0.00, 0.0033, 0.005, 0.010 and 0.020 and three bed stone diameters ds = 5 mm, 10 mm and 15 mm are tested. The laboratory results demonstrated straight line relationships for the variation of end depth ye with critical depth yc and the variation of end depth with uniform normal depth yn for different values of z, St and ds tested in this study, while, the relation between ye/yc and bed slope St showed a quadratic expression. Moreover, the relationship for the dimensionless discharge with both channel bed slope St and the ratio of end water depth ye to bed stone diameter ds (ye/ds) has been presented by a simple empirical power equation with high determination coefficient which can be applied for subcritical and supercritical states of flow for the range of upstream Froude number Frn between 0.14 and 1.27.